Next-Generation Enterprise Solutions: Integrating AI with Business Process Automation - Sasikiran Vepanambattu Subramanyam, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The strategic integration of artificial intelligence with business process automation represents a fundamental reimagining of enterprise operational frameworks in the digital transformation era. This convergence transcends traditional rule-based systems by introducing adaptive intelligence capable of learning from historical data, responding to changing conditions in real-time, making decisions with minimal human intervention, predicting outcomes through pattern recognition, and processing previously untapped unstructured data sources. Across financial services, healthcare, and manufacturing sectors, organizations implementing these technologies have witnessed substantial improvements in operational efficiency, decision quality, and customer experience. However, successful implementation requires thoughtful consideration of data quality and governance, comprehensive change management strategies, and ethical frameworks addressing algorithmic bias, transparency, and accountability. As these technologies continue to evolve, emerging trends including explainable AI, federated learning, and human-AI collaboration will shape future developments, creating new opportunities for operational excellence and competitive differentiation.
Keywords: Automation; Business process; Ethical frameworks; Explainable AI; Machine learning